The culture of community nursing: An ethnographic study of handover reports. - Denise Drew (2008)
This study explores the culture of community nurses exhibited during the time spent together in handover reports. As community nurses spend much of their shifts working alone in patients' houses, this is the time to meet up in clinics and health centres to share information about patient care. Culture is observed through group interactions, behaviour, language, ritual and the use of artefacts and so this handover time provides the opportunity to explore these matters. The research question is: what cultural behaviour, cultural knowledge and cultural artefacts are exemplified during community nurses' handover reports? Using an ethnographic approach, data collection was carried out using participant observation and semi-structured interviews. Two teams of nurses from one Primary Care Trust in the West Midlands participated in this study. The resulting data was analysed using James Spradley's (1979) thematic cultural analysis and the findings are presented in four sections. Findings include: sharing information and planning ahead, helping across teams and busyness, being in the team and how others see us. Issues of community nurses invisibility and the articulation of expertise are presented. Some of the findings were congruent with earlier studies (largely set in hospital or nursing homes) including teaching and learning and support for staff. In addition, this study adds the following considerations to the body of knowledge relating to handover reports. Firstly, the importance of protecting reporting time for community nurses is suggested. In the current social and financial climate it is essential to make the case for continuity of care to be safeguarded. Secondly, the importance of professional identity for community nurses is stressed. The reporting time serves to enhance group identity, reduce anxieties and relieve isolation. Finally, report time crucially encourages the articulation of expertise between community nurses at a time when they are feeling professionally devalued.